NILAI KEADILAN DAN NILAI KEMANFAATAN PADA JARIMAH QISAS DAN DIYAT DALAM HUKUM PIDANA ISLAM - Noercholish Rafid (Rumah Jurnal STAIN Majene, 2022)
This research examines the value of justice and the value of benefit in jarimah qisas and diyat in Islamic criminal law. The type of research is library research using a syar'i normative approach, it is an approach based on the arguments of the Qur'an and hadith. Jarimah qisas diyat applies universally as a form of benefit value for the survival of the community. REFERENCES Abu Zahrah, Muhammad . (1998). Al-Jarimah wa al-‘Uqubah fi al-Fiqh al-Islami. Al-Qahirah: Dar al-Fikr al-‘Arabi Al-Maliki, Abdurrahman & Ahmad ad-Da’ur. (2004). Nidzam al-Uqubat dan Ahkam al-Bayyinat/Sistem Sanksi dan Hukum Pembuktian dalam Islam, Penerjemah,Syamsuddin Ramadlan, Bogor: PustakaThariqul Izzah. Arief, Barda Nawawi. (1998). Beberapa Aspek Kebijakan Penegakan dan Pengembangan Hukum Pidana, Bandung: Citra Aditya Bakti. Arrasid, Chainur. (2004). Dasar-dasar Ilmu Hukum, Jakarta: Sinar Grafika. Asse, Ambo. (2010). Konsep Adil Dalam Al-Qur‟an (Jurnal Al-Risalah Volume 10 Nomor 2. Asshiddiqie, Jimly & M. Ali Syafa'at. (2006). Teori Hans Kelsen Tentang Hukum, Jakarta: Konstitusi Press. Atmasasmita, Romli. (1992). Teori Kapita selekta Kriminologi. Bandung: PT Eresco. Darijarkoro. (1985). PidanaMati di Indonesia, Jakarta: Ghalia. Hadana, Erha Saufan dan Beri Rizqi. (2020) Konsep Keadilan Terhadap Delik Pembunuhan (Analisis Komparatif Hukum Islam dan KUHP), Legitimasi, Vol. 9 No 2. Haliman. (1971). Hukum Pidana Syari’at Islam Menurut Ajaran Ahlus Sunnah. Bulan Bintang, Jakarta. Hamzah, Andi. Sistem Pidana dan Pemidanaan Indonesia Dari Retribusi ke Reformasi. Hanafi. (1990). Asas-AsasHukumPidana Islam, Cet. 4. Jakarta: Bulan Bintang. Helmi, Muhammad. (2015).